TOLERANSI STRATEGI DALAM MEMBANGUN KERUKUNAN ANTARUMAT BERAGAMA DI INDONESIA - Kiki Mayasaroh (Fakultas Agama Islam Universitas Wiralodra, 2020)
The term inter-religious harmony is synonymous with the term tolerance. Harmony is a term that is filled with the contents of good meaning and peace. The point is living together in society with unity of heart and agreeing not to create disputes and quarrels. Living in harmony is everyone's dream. Differences on one hand can be a strength if managed properly and professionally. However, if not, differences in worldview among multicultural nations will be a factor of nation disintegration and prolonged conflict. This article aims to find out how the strategy in building harmony among religious believers in Indonesia. The method used in this study is library research (Literature Study), which is to trace books and findings from studies of interfaith harmony. The results of this study explain that there are 6 strategies that can be carried out in building harmony between religious believers, namely internalizing tolerance, maintaining kinship (ukhuwah), mutual respect and respect, mutual trust and avoiding prejudice, clarifying and confirming the information obtained and acting fairly . Keywords: Strategy, Harmony, Religious people